The Responsible Director in an Economic Downturn: Lessons from the Restriction Regime - Ahern, Deirdre (My University, 2009)
This article discusses the legal duties of directors when a company is in financial difficulties and may be heading towards insolvency.
PUBLISHED
Keywords: Directors' duties; company law